AN ANALYSIS OF CODE-SWITCHING AS FOUND IN TALK-SHOWS - Jon Pieter Situmorang; Sonia Natheni (Muse: Jurnal of Art, 2023)
This article deals with An Analysis of Code-Switching as Found in Talk-Shows. The objectives of this article are to find out the types of code-switching in talk-shows and to find out the reasons of the speakers doing code-switching in talk-shows. The source which is used in collecting the data are five talk-shows on YouTube: they are Catatan Najwa, Ngobrol Sore Semaunya, Vidi-O-Game, The Merry Riana Show and Sarah Sechan. This article used the qualitative research to carry out the study. The theories of Poplack and Hoffman are used in this article. The result of the analysis shows that there are three types of code-switching. From 100 code-switching, there are 59 data of intra-sentential switching, 29 data of inter-sentential switching and 12 data of tag switching. Aside from the three types of code-switching, there are also seven reasons of the speakers doing code-switching. From 100 data there are 32 data of discussing about a particular topic, 3 data of quoting somebody else, 2 data of being emphatic about something (expressing solidarity), 10 data of Interjection (inserting sentence fillers or sentence connectors), 3 data of repetition for clarification, 10 data of intention in clarifying the speech content for interlocutor and 40 data of expressing group identity. And based on the analysis of the study, it is found that the highest number of the types of code-switching is intra-sentential code-switching which attain 59 data. And the main reason of the guests in the talk-shows doing code-switching is expressing their group identity which attain 42 data.